Anatomical distribution of CGRP-containing lumbosacral spinal afferent neurons in the mouse uterine horn - Dodds, Kelsi N.; Kyloh, Melinda A.; Travis, Lee; Cox, Mack; Hibberd, Tim J.; Spencer, Nick J. (Frontiers in Neuroscience, 2022)
Sensory stimuli from the uterus are detected by spinal afferent neurons whose cell bodies arise from thoracolumbar and lumbosacral dorsal root ganglia (DRG). Using an in vivo survival surgical technique developed in our laboratory to remove select DRG from live mice, we recently quantified the topographical distribution of thoracolumbar spinal afferents innervating the mouse uterine horn, revealed by loss of immunoreactivity to calcitonin gene-related peptide (CGRP). Here, we used the same technique to investigate the distribution of lumbosacral uterine spinal afferents, in which L5-S1 DRG were unilaterally removed from adult female C57BL/6J mice (N = 6). Following 10-12 days recovery, CGRP immunoreactivity was quantified along the length of uterine horns using fluorescence immunohistochemistry. Relative to myometrial thickness, overall CGRP density in uterine tissues ipsilateral to L5-S1 DRG removal was reduced compared to the DRG-intact, contralateral side (P = 0.0265). Regionally, however, myometrial CGRP density was unchanged in the cranial, mid, and caudal regions. Similarly, CGRP-expressing nerve fiber counts, network lengths, junctions, and the proportion of area occupied by CGRP immunoreactivity were unaffected by DRG removal (P ≥ 0.2438). Retrograde neuronal tracing from the caudal uterine horn revealed fewer spinal afferents here arise from lumbosacral than thoracolumbar DRG (P = 0.0442) (N = 4). These data indicate that, unlike thoracolumbar DRG, lumbosacral spinal afferent nerves supply relatively modest sensory innervation across the mouse uterine horn, with no regional specificity. We conclude most sensory information between the mouse uterine horn and central nervous system is likely relayed via thoracolumbar spinal afferents.